1999
DOI: 10.1146/annurev.neuro.22.1.11
|View full text |Cite
|
Sign up to set email alerts
|

The Cell Biology of the Blood-Brain Barrier

Abstract: The blood-brain barrier (BBB) is formed by brain capillary endothelial cells (ECs). In the late embryonic and early postnatal period, these cells respond to inducing factors found in the brain environment by adopting a set of defined characteristics, including high-electrical-resistance tight junctions. Although the factors have not been identified definitively, a great deal of information about brain ECs has been obtained, especially recently. This review concentrates on a cell biological analysis of the BBB,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
578
1
8

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 913 publications
(594 citation statements)
references
References 86 publications
7
578
1
8
Order By: Relevance
“…The BBB cells containing tight junctions serve to restrict and control the movement of substances between the systemic circulation and brain extracellular fluid and are characterized by a high TEER and low permeability [8,11,14,18,49,59]. BBB disruption leads to extravasation of plasma proteins into the brain through transcellular and paracellular routes [34,54,63]. Our understanding of the mechanisms that lead to the disruption of the BBB is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BBB cells containing tight junctions serve to restrict and control the movement of substances between the systemic circulation and brain extracellular fluid and are characterized by a high TEER and low permeability [8,11,14,18,49,59]. BBB disruption leads to extravasation of plasma proteins into the brain through transcellular and paracellular routes [34,54,63]. Our understanding of the mechanisms that lead to the disruption of the BBB is limited.…”
Section: Discussionmentioning
confidence: 99%
“…The disruption of the bloodbrain barrier integrity has been shown to occur in many neurological disorders such as Alzheimer's disease, stroke and HIV-1 encephalopathy [34,54,63] but the mechanisms involved in BBB disruption remain incompletely understood. A major limiting factor is the lack of reliable models of the human blood-brain barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical staining showed that the culture system consisted of pure endothelial cells. In vitro models are generally more permeable than the BBB in vivo, but permeability can be decreased by co-culturing the cells with astrocytes (Rubin et al 1991) or by the use of various compounds that cause an elevation of cAMP levels, thereby increasing barrier function (Rubin and Staddon 1999). With these approaches, we were able to obtain relatively high TEER.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, it is guarded by the blood-brain barrier that is impermeable for resting lymphocytes or large effector molecules, such as antibodies. 33 Furthermore, neurons fail to express MHC class I or II determinants and thus provide neither a stimulus nor a target for T cells. 34 Microglial cells and astrocytes can express antigen in the context of MHC class I and II molecules, but their function in antigen presentation is ill defined.…”
Section: Discussionmentioning
confidence: 99%